Enkapsulasi Asap Cair Tandan Kosong Kelapa Sawit (Elaeis guineensis Jacq.) dan Uji Aktivitas Antijamur - Riskawati; Nurul Magfira; Maswati Baharuddin; Sappewali; Fitria Azis (Study Program of Chemistry - Alauddin State Islamic University of Makassar, 2022)
Oil palm empty bunches is lignocellulose that can be processed into liquid smoke with the content of acid compounds and phenol compounds that function as a natural preservative. The purpose of this study to find out the characteristics of liquid smoke, see the effect of encapsulan on the liquid smoke encapsulation process, and see the antifungal activity of A. flavus and A. niger. The method used is pyrolysis process at a temperature of 400 oC to produce liquid smoke and encapsulation process by using variation of coating material using spray dryer with micro sized result. The result showed that the liquid smoke characteristics can be seen from its chemical content that is the dominant phenol compound and has the highest phenol content among the parts found in oil palm that is 68,15%. Based on analysis it can be seen that the best encapsulation process is by the addition of chitosan on maltodextrin with water content 5.78%, phenol content of 43.03 ppm and has a high rate of encapsulation efficiency of 45.87%. The liquid smoke microcapsules could inhibit the growth of fungi with the highest value of liquid smoke concentration, that is 3% with inhibitory value of 8.30 mm.